THE MEANING OF ?ING FORM AS CLASSIFIER IN NOMINAL GROUP: SYSTEMIC FUNCTIONAL LINGUISTICS PERSPECTIVE - Anum Dahlia (Universitas Widyatama, 2019)
The aim of this study is to describe and to classify the meaning of ?ing form in nominal group structure based on systemic functional linguistics perspective. To understand the meanings of ?ing form, it is necessary to know its function in the structure. The existence of ?ing form in nominal group structure can be functioning as Epithet, Classifier, Thing, and Qualifier. This study is done to describe and to classify the meaning of ?ing form functioning as Classifier. This study deserves doing since Classifier has wide range of semantic relations, and the broad meaning needs to be identified, and then to be described and classified based on the characteristics. The results find that the ?ing form describe status and process when it is represented by the word class of verb plus ?ing, then categorized as present participle functioning as verb, but when present participle functioning as adjective, the ?ing form describes restriction related to time and sequence; the ?ing form describes purpose and function, and scope when it is represented by the word class of noun plus ?ing, then categorized as verbal noun functioning as noun; the ?ing form describes restriction associated with science when it is represented by the word class of noun plus ?ing, then categorized as pseudo-participial adjective functioning as noun.